The ‘Double Helix’ model of quality monitoring: Risk mapping of quality management system during initial ISO 15189 Implementation in a medical laboratory - Shuzhe Yang; Yali Zhou; Chunyuan Wang; Mengjun Luo (PLoS ONE, 2026)
Objective Analyze and compare the characteristics of nonconformities (NCs), root causes, and corrective actions generated from internal assessments and ISO 15189 external assessments in a medical laboratory, identify high-risk points and evaluate the role and contribution of different assessments to the medical laboratory’s quality performance. Methods A total of 35 NCs from internal assessments and 67 NCs from external assessments were documented in a medical laboratory between 2021 and 2024. The NCs were categorized according to clause requirements, while root causes and corrective actions were classified based on their content. The recurrence rate of NCs, effectiveness of corrective actions and characteristics of recurring NCs were statistically analyzed. The flow relationships were shown by Sankey diagrams. The laboratory quality monitoring model was illustrated by a double-helix diagram. Results In internal assessments, the top three NC categories were Examination processes (n = 8, 22. 86%), Personnel management (n = 7, 20. 00%), Document and record control (n = 6, 17. 14%);in external assessments the top categories were were Examination processes (n = 19, 28. 36%), Document and record control (n = 10, 14. 93%), Others(Evaluation, Complaints, Information system, Risk Management)(n = 8, 11. 94%), Personnel management (n = 6, 8. 96%). Regarding root causes, the most frequent in internal assessments were Personnel Negligence (n = 14, 40. 00%), Training deficiencies (n = 11, 31. 43%);in external assessments, the tops were Training deficiencies (n = 27, 40. 30%), Document and Record Deficiencies(n = 15, 22. 39%). The The most frequently implemented corrective action across both assessment types was Personnel training(internal [n = 35, 47. 29%] and external [n = 67, 41. 36%]). The numbers of Managment NCs, Technical NCs, total NCs, and Corrective Actions in external assessments were significantly higher than in internal assessments. Conclusion The high-risk points primarily lie in Examination processes, Document/record and Personnel management during the initial implementation of the ISO 15189. External assessments help identify deviations, contributing to quality performance improvement. Internal assessments enable continuous monitoring of quality issue corrections, supporting the ongoing enhancement of the QMS. The ‘Double Helix’ Model of Quality Monitoring ensures the stability and accelerated advancement of the quality management system in the medical laboratory.